Expression of nuclear Ki-67 antigen in prostatic high grade intraepithelial neoplasia and prostatic carcinoma - Janković-Veličković Ljubinka; Đorđević Biljana; Rančić Gorana; Marjanović Goran (Vojnosanitetski Pregled)
Background/Aim. Prostatic intraepithelial high grade neoplasia (PINHG) is accepted as preneoplastic lesion in prostatic carcinoma. One of the fundamental events in early oncogenesis is the disruption of proliferative activity. One of the numerous regulatory proteins is Ki-67 expressed in all proliferating cells. Index Ki-67 is considered to have prognostic significance. The aim of the study was to compare the level of proliferation in hyperplastic epithelium, prostatic carcinoma (Gleason score > 6) and PINHG. Methods. Micromorphological examination was done in 85 patients. Pathohistological analysis was performed on standard histologic specimens with the estimation of Gleason score and the presence of PINHG in its surroundings. Nuclear proliferative activity was analyzed immunohistochemically in 19 cases, using a monoclonal anti-Ki-67 antibody. Results. PINHG was found in prostatic carcinoma surrounding in 30% of the patients. In hyperplastic epithelia Ki-67 proliferative activity was 1,08, in PINHG 2,25 (p < 0,05), while in prostatic cancer, Ki-67 index was 17,64. Proliferative activity in prostatic carcinoma was significantly higher than in PINHG (p < 0,001) and hyperplasia (p < 0,001). Conclusion. This study confirmed that high grade PIN lesion predominately appears in the surrounding of poor or moderately differentiated prostate carcinoma, and that it represents progressive disorder of proliferation in preneoplastic and neoplastic prostatic epithelium. .